Cover Image, Volume 13, Issue 3. (26th March 2019) - Hori, Kanji; Kuwabara, Junichi; Tanaka, Yuji; Nishida, Mitsuhiro; Koide, Naoshi; Takahashi, Masayo
Abstract : The cover image is based on the Research Article A simple and static preservation system for shipping retinal pigment epithelium cell sheets by Kanji Hori et al., https://doi.org/10.1002/term.2805 . © iP‐TEC® Premier BOX‐V8.5/ iP‐TEC® Temperature Stabilizer‐24. Reproduced with permission by Sanplatec Co., Ltd., Osaka, Japan.